Human Leukocyte Antigen (HLA) and Immune Regulation: How Do Classical and Non-Classical HLA Alleles Modulate Immune Response to Human Immunodeficiency Virus and Hepatitis C Virus Infections? - Crux, Nicole B.; Elahi, Shokrollah (Frontiers in Immunology, 2017)
The genetic factors associated with susceptibility or resistance to viral infections are likely to involve a sophisticated array of immune-response. These genetic elements may modulate other biological factors that account for significant influence on the gene expression and/or protein function in the host. Among them, the role of the Major Histocompatibility Complex (MHC) in viral pathogenesis in particular HIV and HCV, is very well documented. We recently added a novel insight into the field by identifying the molecular mechanism associated with the protective role of HLA-B27/B57 CD8+ T cells in the context of HIV-1 infection and why these alleles act as a double-edged sword protecting against viral infections but predisposing the host to autoimmune diseases. The focus of this review will be reexamining the role of classical and non-classical HLA-alleles including class Ia (HLA-A, -B, -C), class Ib (HLA-E, -F, -G, -H) and class II (HLA-DR, -DQ, -DM, and -DP) in immune regulation and viral pathogenesis (e.g. HIV and HCV). To our knowledge this is the very first review of its kind to comprehensively analyze the role of these molecules in immune regulation associated with chronic viral infections.